Redução do crescimento de plantas de crisântemo e lisianthus em vaso - Mainardi, Jucelma de Cássia Camara Tolotti (2013)
The Chrysanthemum (Dendranthema grandiflora Tzvelev) and Lisianthus (Eustoma grandiflorum Raf.) are species of ornamental plants of great prominence in the Brazilian and international floriculture. In the cultivation of ornamental plants in pots, is usually performed chemical control of plant growth seeking its standardization. This research aimed to evaluate the responses of these two species to plant growth retardant, sprayed on cutting cultivars conducted in pots in order to obtain a differentiated product, and also define the optimal dose for producing quality plant pots suited to commercial standards. The survey consists of tests in a randomized design. Lisianthus in the model is 3 x 5 factorial, with three cultivars ('Echo Pure White', 'Mariachi Misty Pink' and 'Echo Yellow') and five doses of Paclobutrazol (0, 16, 32, 48 and 64 mg.L-1) applied in spraying. The Chrysanthemum uses 2 x 4 factorial design, frequency of application being tested weekly and biweekly and plant growth retardant Daminozide (0, 2.000, 4.000 and 6.000 mg.L-1) on the cultivar 'Yellow Spithoven'. The results show that the cultivar of Lisianthus 'Echo Yellow' is the most suitable for growing in pots and the best fit is achieved with these commercial spraying of 64 mg.L-1 of Paclobutrazol. The cultivar of Chrysanthemum 'Yellow Spithoven' has driven its growth Daminozide and can be grown in pots, and 2.000 mg L-1 produces the weekly sprayed potted plants of better quality.